1978
DOI: 10.1136/pgmj.54.635.623
|View full text |Cite
|
Sign up to set email alerts
|

Demeclocycline in the treatment of the syndrome of inappropriate antidiuretic hormone release: with measurement of plasma ADH

Abstract: Summary A patient with the syndrome of inappropriate antidiuretic hormone release (SIADH) following head injury and meningitis was studied during treatment with demeclocycline, a drug known to produce a reversible nephrogenic diabetes insipidus. No changes were observed during six days of demeclocycline 1200 mg/24 hr but urine output increased significantly, with the production of a dilute urine, when the dose was increased to 2400 mg/24 hr. The patient lost weight, and all biochemical features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We also found several observational reports of acute kidney injury with demeclocycline (214,215,218,219,222,223,224,225,226,227,228,229,230,231,232); a single case report of confusion and somnolence with lithium (220) and unspecified neurological abnormalities with phenytoin (233). Finally, we identified two reports of adverse events with fluid restriction.…”
Section: Rationale † Why This Question?mentioning
confidence: 62%
“…We also found several observational reports of acute kidney injury with demeclocycline (214,215,218,219,222,223,224,225,226,227,228,229,230,231,232); a single case report of confusion and somnolence with lithium (220) and unspecified neurological abnormalities with phenytoin (233). Finally, we identified two reports of adverse events with fluid restriction.…”
Section: Rationale † Why This Question?mentioning
confidence: 62%
“…In total, 16 non‐RCTs were considered relevant, comprising six cohort studies (four observational studies 20, 22, 26, 27, two retrospective chart analyses 21, 28, and 10 case reports 29, 30, 31, 32, 33, 34, 35, 36, 37, 38 (Tables 2 and 3, respectively); no cost‐effectiveness or HRQoL studies were identified. Quality assessments for all studies other than case reports are presented (Appendix C).…”
Section: Resultsmentioning
confidence: 99%
“…Ten case reports, detailing 11 patients in total, presented safety data pertaining to demeclocycline 29, 30, 31, 32, 33, 34, 35, 36, 37, 38. Demeclocycline effectiveness and safety data reported in case studies are presented in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations